Gut mucosal immune responses and protective efficacy of oral yeast Cyprinid herpesvirus 2 (CyHV-2) vaccine in Carassius auratus gibelio - Dong, Zhao-Ran; Mu, Qing-Jiang; Kong, Wei-Guang; Qin, Da-Cheng; Zhou, Yong; Wang, Xin-You; Cheng, Gao-Feng; Luo, Yang-Zhi; Ai, Tao-Shan; Xu, Zhen (Frontiers in Immunology, 2022)
Cyprinid herpesvirus 2 (CyHV-2) causes herpesviral hematopoietic necrosis (HVHN) disease outbreaks in farmed Cyprinid fish, which leads to serious economic losses worldwide. Although oral vaccination is considered the most suitable strategy for preventing infectious diseases in farmed fish, so far there is no commercial oral vaccine available for controlling HVNN in gibel carp (C. auratus gibelio). In the present study, we developed for the first time an oral vaccine against CyHV-2 by using yeast cell surface display technology and then investigated the effect of this vaccine in gibel carp. Furthermore, the protective efficacy was evaluated by comparing the immune response of a single vaccination with that of a booster vaccination (booster-vaccinated once 2 weeks after the initial vaccination). Critically, the activities of immune-related enzymes and genes expression in vaccine group, especially in the booster vaccine group, were higher than those in the control group. Moreover, strong innate and adaptive immune responses could be elicited in both mucosal and systemic tissues after receipt of the oral yeast vaccine. To further understand the protective efficacy of this vaccine in gibel carp, we successfully developed the challenge model with CyHV-2. Our results showed the relative percent survival was 66.7% in the booster vaccine group, indicating this oral yeast vaccine is a promising vaccine for controlling CyHV-2 disease in gibel carp aquaculture.